2020
DOI: 10.1177/1178636120913280
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Bioremediation of Feather Waste for Keratinase Production: An Outstanding Solution for Leather Dehairing in Tanneries

Abstract: In leather industries and tanneries, large amount of wastes has been disposed; which polluting water, soil, and atmosphere and causing serious human health problems. In particular, chemical dehairing process of leather industries produces fair amount of toxic wastes. It is, thus, urgently needed to use alternative processes free from pollution. As more than 90% of keratin is contained in feather, it is desirable to develop bioremediation process using keratinolytic microorganisms. In the present investigation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Some general properties of selected keratinolytic proteases are presented in Table 1. Majority of keratinolytic proteases are catalytically active within neutral to alkaline pH with optima values between pH 7.0 and 9.0 (Gradišar et al, 2000;Bach et al, 2011;Kuo et al, 2012;Jaouadi et al, 2013;Bose et al, 2014;Akhter et al, 2020). However, a few extremely alkalophilic keratinases with optimum pH between 10 and 13 were previously reported (Friedrich and Antranikian, 1996;Letourneau et al, 1998;Mitsuiki et al, 2006;Jaouadi et al, 2008Jaouadi et al, , 2010Tatineni et al, 2008;Benkiar et al, 2013;Paul et al, 2014b;Gong et al, 2015;Tian et al, 2019).…”
Section: Biochemical Properties Of Keratinasementioning
confidence: 99%
See 1 more Smart Citation
“…Some general properties of selected keratinolytic proteases are presented in Table 1. Majority of keratinolytic proteases are catalytically active within neutral to alkaline pH with optima values between pH 7.0 and 9.0 (Gradišar et al, 2000;Bach et al, 2011;Kuo et al, 2012;Jaouadi et al, 2013;Bose et al, 2014;Akhter et al, 2020). However, a few extremely alkalophilic keratinases with optimum pH between 10 and 13 were previously reported (Friedrich and Antranikian, 1996;Letourneau et al, 1998;Mitsuiki et al, 2006;Jaouadi et al, 2008Jaouadi et al, , 2010Tatineni et al, 2008;Benkiar et al, 2013;Paul et al, 2014b;Gong et al, 2015;Tian et al, 2019).…”
Section: Biochemical Properties Of Keratinasementioning
confidence: 99%
“…For instance, huge amount of hairs generated during leather processing as by-products are mostly landfilled or composted (Thankaswamy et al, 2018); with high tendency of exuding noxious gases that instigate air pollution due to the load of chemical constituents and microbial activity on the nitrogen-rich biomass (Akhter et al, 2020;Moktadir et al, 2020). Also, the leachate may contaminate the soil and groundwater, which would invariably constitute environmental concern and health risk to the local population (Ammasi et al, 2019).…”
Section: Environmental Impact Of Keratinous Waste and The Ecologicalmentioning
confidence: 99%
“…Isolate P3A exhibited the 84% feather degradation after 96 hrs in whole feather broth medium (Fig 2). Nonso et al 43 39 revealed that complete degradation of feather was obtained within 5 days. Jendri Mamangkey et al 45 reported newly isolated strain Azotobacter chroococcum B4 capable of degrading whole feathers after 5 days.…”
Section: Percentage Of Feather Degradationmentioning
confidence: 98%
“…The enzyme activity was decreases as per increases the incubation time after 96 hrs ( Table 2). Mursheda akhter et al 39 recorded highest keratinase activity 60 U/ml after 96 hrs from the Bacillus cereus and 44 U/ml after 72 hrs from Pseudomonas sp using chicken feather. Similar work of Jahan et al 40 revealed that isolate Z4 showed highest keratinase activity 22.3 U/ml after 72 hrs and complete degradation of feather after 7 days…”
Section: Determination Of Keratinase Activitymentioning
confidence: 98%
“…e products released from the degradation of feathers are rich in amino acids and nutrients and thus can be used as feed additives, fertilizers for plant growth [130], free radical scavengers, ferric ion reducing agent [131], and toxic hexavalent chromium reducing agent [126]. Keratinase is used in enzymatic environment-friendly dehairing processes in the leather industry to replace the traditional chemicals CaO and Na 2 S, which prevent toxic waste release in water bodies to avoid pollution [132].…”
Section: Dehydrogenasementioning
confidence: 99%